Evolución de las relaciones transfronterizas en el Bidasoa: de la conurbación a la communauté - Alberdi Collantes, Juan Cruz (Geographicalia, 2014)
With the ingress of Spain in European Community and the end of the border, international relations are developing. On the other side, neighbours who lived separate now are together. The towns of Bidasoa (Irun, Hendaia and Hondarribia), form a conurbation and they decide to look up the future together. They found the International Consortium of Bidasoa in 1998 but the difficulties of working in two different countries restrict its development. Recently some of they are founding new institutions, gathering villages, and they are overcoming some of the difficulties that the Consortium can not overcome. Now the continuity of the Consortium is in doubt while the new institutions are taking more roles.